2022
DOI: 10.2176/jns-nmc.2022-0095
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Crystals in the Retrieved Thrombus by Mechanical Thrombectomy for Cerebral Embolism: A Case Report and Literature Review

Abstract: There are only a few case reports in which cholesterol crystals were found in the thrombus retrieved by mechanical thrombectomy for cryptogenic stroke, leading to a definitive diagnosis. We herein report a case of aortogenic embolic stroke diagnosed by the presence of rich cholesterol crystals in the retrieved thrombus and review the previously reported cases. A woman in her 80s was transferred as an emergency due to consciousness disturbance, right conjugate deviation, and severe left hemiparesis. Magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Observations Mechanical thrombectomy is now widely performed, and several recent studies have reported the results of pathological analysis of the retrieved thrombus. [5][6][7] In some of these studies, the embolic source could be identified by pathological examination, 8,9 which is invaluable in terms of obtaining a diagnosis. To the best of our knowledge, there is only one reported finding of a fungal mass in a thrombus that had been retrieved by thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Observations Mechanical thrombectomy is now widely performed, and several recent studies have reported the results of pathological analysis of the retrieved thrombus. [5][6][7] In some of these studies, the embolic source could be identified by pathological examination, 8,9 which is invaluable in terms of obtaining a diagnosis. To the best of our knowledge, there is only one reported finding of a fungal mass in a thrombus that had been retrieved by thrombectomy.…”
Section: Discussionmentioning
confidence: 99%